STUDENTS' PERSPECTIVE TOWARD CHALLENGES IN SPEAKING SKILLS DURING SYNCHRONOUS LEARNING VIA WHATSAPP GROUP - Rijal Hengki Adil Al-a (2022)
Abstract During the pandemic era, synchronous learning was used to conduct teaching-learning activities. Even though the method of learning is different from the normal era, students still have to learn English speaking skills during synchronous learning due to the improtant of mastering speaking skills. The Researcher has a curiosity regarding the speaking challenges during synchronous learning. Coming from that curiosity, this research investigated students' perspective towards challenges in speaking skill during synchronous learning via WhatsApp group. The method used in this research was qualitative methods. The instruments in this qualitative research were interview and questionnaire. The participants of this research were 7 students of eleventh grade in SMA in Bandung. This research found that the students believe that facing speaking challenges during synchronous learning is a normal thing. This statement can be strengthened by the findings which indicate that most of the students found shyness and fear of making mistakes even during synchronous learning. Keywords: speaking challenges, synchronous learning, WhatsApp Group.